2011
DOI: 10.5194/acp-11-2747-2011
|View full text |Cite
|
Sign up to set email alerts
|

Sources of carbonaceous aerosol in the Amazon basin

Abstract: Abstract. The quantification of sources of carbonaceous aerosol is important to understand their atmospheric concentrations and regulating processes and to study possible effects on climate and air quality, in addition to develop mitigation strategies.In the framework of the European Integrated Project on Aerosol Cloud Climate Interactions (EUCAARI) fine (D p < 2.5 µm) and coarse (2.5 µm < D p < 10 µm) aerosol particles were sampled from February to June (wet season) and from August to September (dry season) 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 81 publications
2
46
1
2
Order By: Relevance
“…The third protocol is EUSAAR 2 (Cavalli et al, 2010), which has been recently proposed as a standard for carbon analysis on samples collected at European regional background sites. It is noteworthy that few samples analysed in our work by EUSAAR 2 required the last step in oxidising atmosphere to be prolonged in order to obtain a complete carbon evolution, as previously reported by other authors (Kuhlbusch et al, 2009;Gilardoni et al, 2011).…”
Section: Thermal-optical Transmittance Analysissupporting
confidence: 58%
“…The third protocol is EUSAAR 2 (Cavalli et al, 2010), which has been recently proposed as a standard for carbon analysis on samples collected at European regional background sites. It is noteworthy that few samples analysed in our work by EUSAAR 2 required the last step in oxidising atmosphere to be prolonged in order to obtain a complete carbon evolution, as previously reported by other authors (Kuhlbusch et al, 2009;Gilardoni et al, 2011).…”
Section: Thermal-optical Transmittance Analysissupporting
confidence: 58%
“…On the other hand, these data points were associated with fairly low aerosol volume concentrations, PV 10 < 1 µm 3 cm −3 . Aerosol chemical characterization at the study site showed that light absorption of BC particles in relatively clean air masses was enhanced by coating effect; this would increase the contribution of absorption to aerosol extinction, increasing the single scattering albedo (Gilardoni et al, 2011). Another explanation could be that some smallscale combustion sources were located in the vicinity of the station so that particle volume did not have time to grow by formation of secondary scattering material (i.e.…”
Section: Aerosol Number Volume and Optical Propertiesmentioning
confidence: 99%
“…Quartz and paper filters were not pretreated prior to analysis. Fine particles (aerodynamic diameter below 2.5 µm) and coarse particles (aerodynamic diameter between 2.5 and 10 µm) were collected simultaneously every 6 days for a collection period of 24 h starting from 08:00 a.m. LT. To avoid negative sampling artefacts due to volatilization of ammonium nitrate from the quartz substrates, a Whatman 41 paper filter was sampled on the back of each quartz filter and the concentration of ammonium and nitrate were calculated as the sum of quartz and paper concentrations (Gilardoni et al, 2009(Gilardoni et al, , 2011. Denuder units were employed to avoid positive sampling artefacts due to absorption of gas species on the sampling substrate.…”
Section: Aerosol Sampling and Analysis Of Chemical Compositionmentioning
confidence: 99%
“…Natural biogenic aerosol comprises up to 80 % of PM 10 aerosol mass, with most of the mass (approx. 70 %) in the coarse mode fraction (Echalar et al, 1998;Gerab et al, 1998;Gilardoni et al, 2011). Biogenic particles consist of particles primarily emitted by the vegetation (e.g.…”
Section: T Pauliquevis Et Al: the Role Of Biogenic Contributionmentioning
confidence: 99%